THE IMPORTANCE OF INDEPENDENT EDUCATION IN HIGHER EDUCATION AND THE THEORETICAL MODEL OF ITS ACTIVITY (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article presents the theoretical and functional structure of the activation of the requirements of independent learning through the design of educational activities on the example of general professional disciplines. It also shows the pedagogical process, the pedagogical system and its stages, algorithms of educational activities, didactic materials needed to activate the independent learning of students.